2010
DOI: 10.1016/j.vetmic.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

A study on the severity and relevance of porcine circovirus type 2 infections in Dutch fattening pigs with respiratory diseases

Abstract: 18This study was set up to get more insights in the severity and relevance of porcine circovirus type 2 (PCV2) infections in 27(pneumonia) at slaughter, and the 8 "low" herds had low percentages of pneumonia at slaughter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 13 publications
1
23
0
1
Order By: Relevance
“…The presence of pleuritis, irrespective of severity of those lesions, has previously been associated with a reduction in weight gain (Hartley et al, 1988;Jäger et al, 2010;Wellenberg et al, 2010). In our study, pigs with pleuritis were on average 1.24 kg lighter than those without lesions at the individual level.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The presence of pleuritis, irrespective of severity of those lesions, has previously been associated with a reduction in weight gain (Hartley et al, 1988;Jäger et al, 2010;Wellenberg et al, 2010). In our study, pigs with pleuritis were on average 1.24 kg lighter than those without lesions at the individual level.…”
Section: Discussionsupporting
confidence: 61%
“…Economic losses associated with pleuritis can be attributed to slow growth and reduced feed conversion (Wellenberg et al, 2010). Infections with M. hyopneumoniae result in significant losses to the pig industry through reduced weight gain, decreased feed efficiency and increased days to slaughter (Thacker and Minion, 2012) the most serious effects of which are seen in the finishing stages (Straw et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Pasteurella multocida is an agent of major importance within the PRDC, and several Brazilian studies (Borowski 2001, Morés 2006, Borowski et al 2007, Kich et al 2007, Heres 2009 and international studies (Kim et al 2003, Ono et al 2003, Cappuccio et al 2004, Pijoan 2006, Hansen et al 2010, Wellenberg et al 2010, Pors et al 2011, 2016 have reported its role. In this study, the involvement of P. multocida with severe respiratory disease in finishing pigs was evaluated, confirming the co-infection of this agent with Influenza type A virus and M. hyopneumoniae but not with PCV2.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, P. multocida is considered to be a secondary infection, aggravating pulmonary infections caused by M. hyopneumoniae and PCV2 (Kim et al 2003, Pijoan 2006, Hansen et al 2010, Wellenberg et al 2010, Fablet et al 2011, Pors et al 2011. However, researchers in southern Brazil (Borowski 2001, Morés 2006, Borowski et al 2007, Kich et al 2007 and Argentina (Cappuccio et al 2004) have suggested that P. multocida is a primary agent capable of causing severe respiratory disease, nevertheless its pathogenesis and invasiveness mechanisms are not clearly described yet.…”
Section: Introductionmentioning
confidence: 99%
“…Alban and others (2013) have previously reported a similar observation in Denmark, where the increased use of vaccines against respiratory diseases (including PCV-2-related infections) corresponded to a decline in the use of antimicrobials for the treatment of respiratory infections in all age groups. PCV-2-triggered immunosuppression has frequently been reported to enable secondary bacterial infections to develop (Segalés and others 2004, Kixmöller and others 2008, Wellenberg and others 2010). This effect may substantially increase the need for antimicrobials among PCV-2-infected pigs (Jensen and others 2010, Vigre and others 2010).…”
Section: Discussionmentioning
confidence: 99%